Evaluation of liver echotexture in healthy cows using computer-assisted program - Erkiliç, Ekin Emre (Slovenian veterinary research, 2025)
This study was aimed at the determination of the echotexture findings of the liver using computer-assisted programmes, and the investigation of the correlation between these findings and some biochemical parameters in healthy cattle. The study material comprised of 18 healthy Brown Swiss cows. The B-mode images acquired were used for the measurement of the mean grey value, homogeneity, contrast, liver depth, portal vein depth, portal vein diameter, hepatic vein diameter and hepatic vein depth. Contrast, homogeneity and mean grey value were determined as 52.23±3.858, 0.18±0.006 and 102.27±5.617, respectively. Despite being statistically insignificant, the mean grey value was negatively correlated with the albumin level (r=-0.311, p>0.05), and positively correlated with the BHBA concentration (r=0.328, p>0.05) and SDH activity (r=0.402, p>0.05). Liver depth and portal vein depth were measured as 129.35±3.441 mm and 105.38±3.263 mm, respectively. BHBA concentration was found to be signifi-cantly and positively correlated with liver depth and portal vein depth (r=0.523, p<0.05 and r=0.663, p<0.01, respectively). In result, an echotexture analysis of the liver was performed in healthy cattle using computer-assisted programmes, the correlation of the echotexture findings with some biochemical parameters was determined, and nu-meric data that could aid in assessment were generated using USG (ultrasonography) as a non-invasive method. While it is considered that mean grey values determined with computer-assisted programmes and hepatic and portal vein depths measured by USG could be used as indicative parameters for negative energy balance, there is need for further research on a greater number of animals.
Keywords: cow; echotexture; liver; mean grey value; portal vein depth